Development of rust disease in cotton as influenced by weather parameters - E. NARAYANA, S.L. BHATTIPROLU*, V. CHENGA REDDY and (Indian Phytopathology, 2016)
The effect of weather factors on the development of cotton rust in different varieties and Bt cotton hybrids was investigated during kharif 2005-2014 at Regional Agricultural Research Station, Lam, Guntur under rainfed conditions. The development of rust during different years in the same varieties/hybrids showed similar trend. Correlation analysis of pooled data indicated strong correlations between rust intensity and sun shine hours and evaporation in Bunny BG II, Jadoo BG II and RCH 2 BG II hybrids. In Narasimha variety significant correlation was observed with evaporation while sun shine hours were significant in L 761. Positive and significant correlation of evening relative humidity was recorded in Bunny and Bunny BG II hybrids. Multiple regression analysis of pooled data showed that weather parameters including morning relative humidity, evening relative humidity, sun shine hours and evaporation significantly influenced the development of rust disease.